Institutional Logic Migration and Industry Evolution in Emerging Economies: The Case of Telephony in India. (5th September 2013) - Jain, Sanjay; Sharma, Deepali
Abstract : We employ a historical case narrative of the Indian telephony sector to inductively develop a process model of institutional change in an industry within an emerging economy. Our findings highlight the turbulent nature of migrating institutional logics—one that involves processes we term subverting, maneuvering and bolstering. We demonstrate how these institutional dynamics impact entrepreneurial activity and explicate the role of the state as a constrained institutional entrepreneur in these scenarios. In highlighting the contested and capricious nature of such migration, we make contributions to the institutions‐based view of strategy and entrepreneurship and the institutional logics and institutional entrepreneurship literatures. Copyright © 2013 Strategic Management Society.